Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.2527/1995.731296x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex class on nutrient content of meat from young goat.

Abstract: The effect of sex class on proximate composition and cholesterol, vitamin, mineral, and fatty acid content was determined for carcass composite samples of cooked goat meat. Soft tissues (fat and lean) from dissection of one side of seven carcasses each for female, castrate, and intact male Florida native or F1 crosses of Florida natives with Nubian or Spanish goats were ground, formed into patties, and then broiled. Also, a leg slice was removed from the side not used for dissection, broiled, and then sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 16 publications
1
18
2
3
Order By: Relevance
“…Cholesterol contents reported in the present study were below the range (518 to 741 g/kg) reported by Madruga et al (2001) for goats raised in semi-extensive system, as well as those reported by Park et al (1991) and Johnson et al (1995).…”
Section: Rearing Systemcontrasting
confidence: 92%
“…Cholesterol contents reported in the present study were below the range (518 to 741 g/kg) reported by Madruga et al (2001) for goats raised in semi-extensive system, as well as those reported by Park et al (1991) and Johnson et al (1995).…”
Section: Rearing Systemcontrasting
confidence: 92%
“…For Johnson et al (1995), castration has no effect on the cholesterol content of goat meat; however, in the present experiment, when analyzing the edible portion of the shoulder, it can be stated that castration had effect (p = 0.0001) on the cholesterol content of sheep meat inducing changes in composition with age because cholesterol is a complex lipidsteroid substance strongly present in animal fats. Therefore, the lambs castrated by hormone action have to deposit more fat in the meat with advancing age thus increasing the cholesterol content.…”
Section: Discussionmentioning
confidence: 47%
“…Os teores de fosfolipídeos e colesterol estão compatíveis com valores reportados para raças exóticas caprinas por Prabhakan e Rao (1983); Park et al (1991) e Johnson et al (1995).…”
Section: Resultsunclassified
“…Nenhum dado foi encontrado na literatura enfocando a variação do teor de colesterol com a idade em carne caprina, no entanto Bragagnolo (1997) reportou um decréscimo significativo no percentual de colesterol em carne suína com o avanço da idade de abate. Johnson et al (1995) .…”
Section: Resultsunclassified